Free radicals in patients with post-traumatic stress disorder - Tezcan, E; Atmaca, M; Kuloglu, M; Ustundag, B (Springer Heidelberg, 2003)
There is mounting evidence indicating that reactive free radical species (FRs) are involved in initiation and development of many different forms of human pathologies including psychiatric disorders. In the present study, we aimed to determine whether antioxidant enzyme (glutathione peroxidase, GSH-Px; superoxide dismutase, SOD and catalase, CAT) activities and malondialdehyde (MDA) levels, a product of lipid peroxidation, were associated with post-traumatic stress disorder (PTSD). The study comprised 14 patients who had been diagnosed with PTSD according to DSM-IV criteria and met the admission criteria and 14 healthy controls. The activities of GSH-Px SOD, CAT and MDA were measured in both the patients and controls. In addition, all patients were assessed using the Clinician Administered PTSD Scale (CAPS). The mean GSH-Px, SOD, CAT activities and MDA levels of the patient group did not differ from those of the controls. However, in patients, the GSH-Px and SOD activities were significantly and positively correlated with CAPS scores, while there was a trend toward positive correlations between CAPS scores and MDA or CAT. In conclusion, our results suggest that the production of FRs does not seem to be related to PTSD.
Keywords: PTSD; antioxidant enzyme; MDA; lipid peroxidation